In Tribute to the Kuwaiti Poet Ali Al-Sabti - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2021)
This is a eulogy of the Kuwaiti poet and writer Ali Hussein Al-Sabti, who died at the age of 86. He was a prominent poet of Kuwait who contributed to the beginnings of the modern poetic movement in Kuwait, writing literary and social stories and articles subsequently published in Kuwaiti and Arab newspapers. He served as a member of the Writers Association and the Journalists Association and wrote for many Kuwaiti newspapers. He also won many awards and honors from authorities and institutions sponsoring poetry and literature, including the Abdulaziz Saud Al-Babtain Prize for Poetic Creativity. The National Council for Culture, Arts and Letters mourns this man who enjoyed a busy journey in literary and cultural work marked by elaborate poems and distinguished writings. The death of Al-Sabti, a great poet and writer, marks a loss for the cultural and literary movement in Kuwait.